2017
DOI: 10.1007/s11136-017-1757-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of French Canadian parents raising a child with autism spectrum disorder and effects of psychosocial factors

Abstract: Beyond the parents' actual situation, our results underscore the importance of paying attention to their own perception of the situation in order to provide them with appropriate support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 74 publications
1
16
0
3
Order By: Relevance
“…When the demographic data of the patients participating in our study were examined; 58 (84.1%) of 69 patients were boys and 11 (15.9%) were girls. Although it is generally accepted that ASD is seen 3-4 times more in males, similar to the findings of some studies, the rate of boys/girls was found to be higher in our study as 5.27 (19).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…When the demographic data of the patients participating in our study were examined; 58 (84.1%) of 69 patients were boys and 11 (15.9%) were girls. Although it is generally accepted that ASD is seen 3-4 times more in males, similar to the findings of some studies, the rate of boys/girls was found to be higher in our study as 5.27 (19).…”
Section: Discussionsupporting
confidence: 87%
“…Sociodemographic Data Form includes a total of 35 questions covering the sociodemographic characteristics of patients and their parents, the history of the patients, co-morbid diseases accompanying the disease, and drug treatments. The scale includes five sub-scales of "alienation" (1,5,8,16,17,21), "stereotype endorsement" (26,10,18,19,23,29), "discrimination experience" (3,15,22,25,28), "social withdrawal" (4,9,11,12,13,20) and "stigma resistance" (7,14,24,26,27). The items on the scale are rated with a four point likert scale: "strongly disagree" (1 point), "disagree" (2 points), "agree" (3 points), "strongly agree" (4 points).…”
Section: Sociodemographic Data Formmentioning
confidence: 99%
“…Plusieurs études mettent en évidence les répercussions négatives de l'autisme, sur différents plans de la vie des familles (Bobet & Boucher, 2005), engendrant entre autres des discontinuités significatives dans la vie familiale, avec des effets distincts sur les parents et la fratrie (Jagla, Schenk, Hampel, Bullinger, & Franke, 2016). D'une manière générale les études antérieures rapportent une qualité de vie plus pauvre pour les familles d'enfant porteur d'un TSA, quel que soit l'âge de l'enfant, lorsqu'elle est comparée à d'autres types de population, et ce (Vasilopoulou & Nisbet, 2016 (Cappe et al, 2009;Cappe, Poirier, Sankey, Belzil, & Dionne, 2018;Cappe et al, 2011), ces études québécoises s'intéressant particulièrement à la façon dont les parents perçoivent leur propre situation et les stratégies de faire face mises en place. Il importe de noter une récente étude comparative entre trois régions francophones : France-Québec-Belgique (Cappe, Pedoux, Poirier, Downes, & Nader-Grosbois, 2019).…”
Section: Qualité De Vie De La Famille Dans Le Tsaunclassified
“…Pour les parents, vivre avec un enfant, un adolescent ou un adulte qui présente une DI ou un TSA, ainsi que les comorbidités pouvant être associées à ces conditions, vient accroître les exigences en soutien et soins à prodiguer. D'ailleurs plusieurs études mettent en lumière que les parents vivant avec un enfant qui présente une DI ou un TSA expérimentent un niveau de stress élevé et sont particulièrement à risque d'épuisement et de détresse psychologique (Cappe et al, 2018 ;Ludlow, Skelly et Rohleder, 2012 ;Protecteur du citoyen, 2012). À ce sujet, une recension des écrits réalisée par Courcy et Des Rivières-Pigeon (2013) met en exergue que jusqu'à 50 % des mères d'enfants présentant un TSA vivraient avec un niveau de détresse élevé.…”
Section: Introductionunclassified